2016
DOI: 10.18517/ijaseit.6.3.809
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an Internal Combustion Engine Derating Operated on Producer Gas from Coal and Biomass Gasification

Abstract: Producer gas is yield gases from gasification that can be burned, composed by CO, H 2 , and CH 4 , and non-combustible gases like CO 2 and N 2. Producer gas utilization for internal combustion engine has been studied, not only from biomass gasification but also from coal gasification. This paper compares the research that has done author using coal gasification with other research results using biomass gasification. Coal gasifier performance test conducted with capacity of 20 kg/h of coal. The proximate and ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The uniqueness of this dryer relied mainly on the shape of the structure as depicted in Figure 1, the design of the heat exchanger as described in detail above, and free from electricity dependence which makes it possible for application in remote areas. Furthermore, the performance of the heat collector may be improved by adopting a solar tracking system [35] while the efficiency of the furnace can be increased since it was found that the gasifier efficiency for biomass was between 50-80% [36]. Finally, the operation of the dryer may be optimized seeing that a device for future solar irradiance prediction may soon be available [37].…”
Section: Resultsmentioning
confidence: 99%
“…The uniqueness of this dryer relied mainly on the shape of the structure as depicted in Figure 1, the design of the heat exchanger as described in detail above, and free from electricity dependence which makes it possible for application in remote areas. Furthermore, the performance of the heat collector may be improved by adopting a solar tracking system [35] while the efficiency of the furnace can be increased since it was found that the gasifier efficiency for biomass was between 50-80% [36]. Finally, the operation of the dryer may be optimized seeing that a device for future solar irradiance prediction may soon be available [37].…”
Section: Resultsmentioning
confidence: 99%
“…Cold gas efficiency (CGE) has a value which was still low at 26.31% compared to gasification which have efficiency 50-70% [18]. It is caused by two factors, namely the calorific value fuel gas produced was still low and the remainder of the conversion of coal powder were still mostly in the form of charcoal.…”
Section: Combustible Yield Gasmentioning
confidence: 99%
“…Chaves et al [13] conducted a study on spark ignition engines using gasoline (single fuel) and producer gas (single fuel) from wood waste gasification, and test results show that the producer gas reduced nominal power by 50%. Efendi et al [14] tested producer gas, produced from coal gasification, as a single fuel in a spark ignition engine. The results of the test showed a decrease in electric power by 46% when using the producer gas as fuel.…”
Section: Introductionmentioning
confidence: 99%